Analytical study of the Fishbone Warehouse layout (2012)
The purpose of this paper is to study the Fishbone Warehouse layout. Fishbone layouts are non-traditional designs for warehouses that have shown to be more efficient under unit-load operations. This paper presents an analytical study of the design from an optimisation point of view. The authors gain an insight into the characteristics of the layout and present alternatives for different situations of interest in industrial environments. Finally, the authors compare the performance of Fishbone and traditional designs; presenting a formal conception of the expected savings. The authors focus on finding optimal conditions for the most important characteristic of the Fishbone design, which is the slope of the diagonal cross-aisle. The design decisions are modelled as a non-linear optimisation problem and solved using both numerical and exact methods, depending on the most convenient analysis. In addition, the robustness of the results is presented and their practical implications discussed.